MODELLING OF ZONES OF POTENTIAL EARTHQUAKES FOCI FOR TERRITORIES NEAR BENIOFF ZONES - Marina Yu. Andreeva; Vyacheslav N. Patrikeev (Геодинамика и тектонофизика, 2015)
Based on the catalogue of earthquakes of the Kuril-Kamchatka region for the period from 1737 to 2007, a 3D model may zones of potential earthquake foci is developed for the Southern Kuril territory. The model can be useful for seismic hazard forecasting. Boundaries of structural elements of the zones with potential earthquake foci are determined by seismic methods.